The Analysis of Basic Structure of Company Assets, Its Differentiation and Variability over Time, on the Basis of Food Industry in Poland - Anna LUDWICZAK (Communications of International Proceedings, 2021)
Industry statistics often constitute a great resource to determine certain regularities while conducting company operations’ analysis. It concerns financial analysis: different kinds of indicators are compared with industry indicators and noticeable deviations are discussed. It is, however, questionable if a particular industry is homogenous or diversified, and thereby if it is possible to use, for example, average figures in a comparative process. It seems that information regarding arithmetical mean is far insufficient. Particular characteristics of population does not have to reflect normal distribution. There can be right side or left side distribution, slender or flattened distribution. It can also indicate sizeable differences and additionally, it is subjected to many changes over time. The aim of this article is investigating the structure of assets of Polish food industry companies listed on the Stock Exchange. The research is based on characteristics of central tendency measures, dispersion measures, asymmetry measures and concentration measures in search for the answer to a question: What additional measures or ways of presenting industry figures could facilitate financial analysts’ work, and thus minimize errors within comparative analysis.
Keywords: Management of Company Assets; Property Management; Financial Analysis; Financial Indicators.